Child Relativized Minimality and Grammaticality Judgement - Gavarró, Anna (Frontiers in Psychology, 2020)
Grammaticality judgments are the fundamental experimental source of generative linguistic theory. They may difficult to elicit, especially in some populations, but generally they inform us neatly about what the grammar licenses or, on the contrary, bans. On the other hand, acceptability is multifactorial and, therefore, unlike grammaticality judgment, can be quantified. In this paper I consider a particular empirical domain, that of Relativised Minimality (RM) in acquisition, and its relation to the dichotomy between grammaticality and acceptability. Friedmann, Belletti & Rizzi (2009) argued that children hold a stricter version of RM than adults. In particular, children would require a disjoint feature specification, not just a distinct feature specification, between target and intervener. The literature shows asymmetries in comprehension of subject and object relative clauses in various languages which fulfil the predictions of child RM. Variation between adults and children might be expected not only in production and comprehension, but also in grammaticality judgment. If so, children would be predicted to reject the classical RM violations and object relatives. Alternatively, if child RM is a processing effect, the prediction is that children would be able to tease apart object relative clauses from RM violations under favourable processing conditions. The question I address is: do children assimilate RM violations and object relative clauses? Grammaticality judgement should provide an answer to this question. In this paper I design an experiment targeting grammaticality judgment for object relatives and RM violations and report preliminary results for a group of 6-year-old Catalan-speaking children.